PARADIGMA BARU MANAJEMEN PENDIDIKAN PADA MADRASAH MENGHADAPI TANTANGAN ZAMAN - ., Mutakallim; Gani S, Abd (Universitas Islam Negeri Alauddin Makassar, 2020)
In the view of Islamic teachings, everything must be done in an orderly, correct, and orderly manner. The processes must be followed properly and should not be done carelessly. Starting from the smallest matters such as managing household affairs to the largest matters such as managing the affairs of a country, all that requires good, precise and directed arrangements within the framework of a management so that the goals to be achieved can be achieved and can be completed efficiently and effectively. Quality Improvement Management which is a new paradigm for education management in Madrasahs has the principles (1) Quality improvement must be carried out in madrasah, (2) Quality improvement can only be carried out with good leadership, (3) Quality improvement must be based on good data and facts qualitative and quantitative in nature, (4) Quality improvement must empower and involve all elements in madrasah, and (5) Quality improvement has the aim that madrasah can provide satisfaction to students, parents and the community.In essence, the goal of educational institutions is to create and maintain customer satisfaction and in TQM customer satisfaction is determined by the educational institution's stakeholders. Because it is only by understanding the process and customer satisfaction that an organization can realize and value quality. All efforts management in TQM must be directed at a main goal, namely customer satisfaction, what management does is useless if it does not create customer satisfaction.